Evaluasi Penjadwalan Waktu Dan Biaya Menggunakan Metode Cpm Pada Proyek Fabrikasi Cyclone - Hidayatulloh, Faishal; Iriani, Iriani (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Project management is an effort to control projects by paying attention to time and resource availability. This control is necessary to achieve targets as planned. The aim of this research is to evaluate work time and project costs using the CPM method for the cyclone making project at PT Putra Dharma Kencana in Mojokerto district. This research uses quantitative approach techniques which are analyzed using CPM and Gantt Chart using POM QM software. In this project there are 10 activities in the order, namely A-B-C-D-E-F-G-H-I-J, the project was planned to be completed in 84 days, but was completed in 98 days. The results of the CPM analysis show 2 activity paths with the critical path, namely A-E-F-G-H-I-J with a time of 62 days. The results of the Gantt Chart analysis of activities that can be done simultaneously are activities B and E on the 7th day, activities C and E on the 14th day, and activities D and F on the 21st day. By implementing the CPM method, costs can be reduced from IDR 48,720,000 to IDR 23,560,000.